Artificial Immune Systems Applied in Data Management Solutions to the Problem of Restoration of Electrical Distribution Systems - Cossi, Antonio Marcos [UNESP]; Martins Lopes, Mara Lucia [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2016)
This paper proposes a method based on Artificial Immune Systems for data management solutions provided by a model used to train power grid and find possible solutions to the problem of restoration of electricity distribution systems. The method aims to manage the supply of recurring defects solutions in the power grid through information stored in a database; the network training for non-recurring defects and storage of data in the database; choosing solutions in the database to start the network training process in the search for new solutions. To train the network and find new solutions to the restoration problem, we use a model that has as one solution technique Tabu Search algorithm. To test the efficiency of the proposed method, we present results of tests and discussions carried out in a medium voltage distribution system.
Keywords: artificial immune systems; Data management; distribution systems; restoration